2020
DOI: 10.1021/acs.energyfuels.9b03217
|View full text |Cite
|
Sign up to set email alerts
|

PbCl2 Capture by Kaolin and Metakaolin under Different Influencing Factors of Thermal Treatment

Abstract: With dramatically increasing emission of heavy metals and chlorinated compounds from thermal treatments of fuels and wastes, kaolin, one of the widely used materials in the industry, was researched to control these pollutants in recent years. To investigate the retention of lead chloride (PbCl2) by kaolin and metakaolin obtained from thermal activation of kaolin, the PbCl2 adsorption experiment in a two-stage furnace was conducted from 600 to 900 °C under N2, H2O, and O2. Furthermore, the toxicity leaching pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…To clarify into which species the adsorbed lead was captured by could reveal its adsorption behaviour, so a leaching test was conducted and these results are shown in Figure 6(b). The proportions of leached form lead for all sorbents decreased with increasing temperature, which means the diffusion of lead from the sorbent surface into the silicates lattice was accelerated by heating (Yu et al, 2020). Moreover, all partition values were below 0.1 at 900 °C, where the apparent melting phenomenon occurred in SEM images for all samples, indicating that most of the lead in the sorbents at high temperature was stabilised and removed to a limited extent by leaching from the adsorption product (Zha et al, 2018).…”
Section: Characteristics Of Adsorption Productmentioning
confidence: 91%
See 3 more Smart Citations
“…To clarify into which species the adsorbed lead was captured by could reveal its adsorption behaviour, so a leaching test was conducted and these results are shown in Figure 6(b). The proportions of leached form lead for all sorbents decreased with increasing temperature, which means the diffusion of lead from the sorbent surface into the silicates lattice was accelerated by heating (Yu et al, 2020). Moreover, all partition values were below 0.1 at 900 °C, where the apparent melting phenomenon occurred in SEM images for all samples, indicating that most of the lead in the sorbents at high temperature was stabilised and removed to a limited extent by leaching from the adsorption product (Zha et al, 2018).…”
Section: Characteristics Of Adsorption Productmentioning
confidence: 91%
“…No peak representing lead content was detected in XRD curves, which could be due to the little mass of sorbate used in the test, while PbSi2Al2O8 has been reported as a product of reaction between kaolin and lead in some literature (Linak et al, 1993;Yu et al, 2020), following these reaction equations:…”
Section: Characteristics Of Adsorption Productmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicated that NO and SO 2 in flue gas could be transformed into nitrate and sulfate under the catalysis of Fe 2 O 3 . 31,32 Based on this fact, some valuable conclusions could be gained. The formed sulfate occupied the active sites on the surface of the adsorbent and further limited the fixation of arsenic, while the generated nitrate possessed oxidizability and could facilitate the transformation of As(III) in flue gas to As(V), 33 which explained why NO promoted arsenic capture at 1000 °C, as shown in Figure 9.…”
Section: Methodsmentioning
confidence: 99%